2010
DOI: 10.1371/journal.pone.0012088
|View full text |Cite
|
Sign up to set email alerts
|

Sox6 Is Necessary for Efficient Erythropoiesis in Adult Mice under Physiological and Anemia-Induced Stress Conditions

Abstract: BackgroundDefinitive erythropoiesis is a vital process throughout life. Both its basal activity under physiological conditions and its increased activity under anemia-induced stress conditions are highly stimulated by the hormone erythropoietin. The transcription factor Sox6 was previously shown to enhance fetal erythropoiesis together and beyond erythropoietin signaling, but its importance in adulthood and mechanisms of action remain unknown. We used here Sox6 conditional null mice and molecular assays to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 58 publications
1
36
0
2
Order By: Relevance
“…This might reflect both the accelerated erythroid differentiation induced by Sox6 (Bcl-xL is known to increase in late erythroid differentiation) and a possible direct transcriptional activation on Bcl-xL, in agreement with what happens in mouse erythropoiesis. 12 In the latter case, the activation of Bcl-xL by Sox6, counteracting the parallel down-regulation imposed by SOCS3, might play a relevant role in ensuring the proper balance between proliferation and cell cycle withdrawal required for terminal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might reflect both the accelerated erythroid differentiation induced by Sox6 (Bcl-xL is known to increase in late erythroid differentiation) and a possible direct transcriptional activation on Bcl-xL, in agreement with what happens in mouse erythropoiesis. 12 In the latter case, the activation of Bcl-xL by Sox6, counteracting the parallel down-regulation imposed by SOCS3, might play a relevant role in ensuring the proper balance between proliferation and cell cycle withdrawal required for terminal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In particular, Sox6, originally isolated from adult mouse testis, 4 is required for the development of the central nervous system, [5][6][7] for chondrogenesis, 8 and for cardiac and skeletal muscle formation. 9,10 Recently, Sox6 has been demonstrated to be crucial for definitive erythropoiesis, [11][12][13][14][15] a process in which committed progenitors progressively differentiate into burst-forming-unit erythroid cells and colonyforming-unit (CFU) erythroid cells, which in turn give rise to proerythroblasts and erythroblasts and finally to mature, enucleated red blood cells. These differentiation stages are accompanied by profound maturational changes: Within few cell divisions, in parallel with the accumulation of erythroid-specific markers (membrane proteins, enzymes required for the heme biosynthesis pathway, and globins), cells undergo chromatin condensation and enucleate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its role in adult erythropoiesis and repression of embryonic/fetal hemoglobin expression, the SOX6 transcription factor is an attractive candidate. 16,17 Alternatively, post-translational modifications and subcellular localization of KLF1 could be involved. 18 Thus, the current work sheds some light on the conundrum that KLF1 is already a functional transcriptional activator in embryonic erythroid cells which do not express adult hemoglobin.…”
Section: A B Cmentioning
confidence: 99%
“…Loss of function experiments showed that SOX6 is a gammaglobin repressor. 11,12 When over-expressed, however, it stimulates cell differentiation and the expression of all globin genes, although the gamma-globin gene is considerably less activated, presumably due to the specific repressive effect of SOX6. 13 In R-cells, SOX6 is over-expressed, particularly after HU administration.…”
mentioning
confidence: 99%